Studi Komparatif terhadap Batasan Usia Pernikahan Dini Perspektif Undang-undang Nomor 16 Tahun 2019 tentang Perkawinan dan Undang-undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Hamzah, Muhammad (AHKAM, 2023)
This research examines the problems that have always occurred in society and are difficult to eliminate, both from the past to the present, which is none other than the case of early marriage. Where this case penetrated all over the country where the perpetrators were not only for the upper middle class but also the lower middle class as happened to the fishing community in Pantai Cermin District, Serdang Bedagai Regency. Marriage actors are not only caused by deviant associations, but sometimes there are indications from certain persons who instead use children as objects to take advantage of them. In fact, if you look deeper into the practice of underage marriage, it will certainly have a significant impact on the child. Moreover, the government has also stipulated terms and conditions for the permissibility of carrying out marriages through laws such as Law Number 16 of 2019 concerning Marriage and Law Number 35 of 2014 concerning Child Protection which the author will examine in more depth. The problems raised in this study contain how according to the provisions of Law Number 16 of 2019 concerning Marriage and Law Number 35 of 2014 concerning Child Protection in deciding the age limit for early marriage and knowing the relevant opinions between the two provisions of the Law will problems that occur in fishing communities in Pantai Cermin District. The method used is comparative juridical empirical method. The main data sources in this study are Law Number 16 of 2019 and Law 35 of 2014 as well as interviews with fishing communities and several informants, namely the community/community leaders in Pantai Cermin District. In addition to the main data, the authors also include other additional data sources in the form of books, journals, previous research studies and other scientific works as data reinforcement.